2012
DOI: 10.1163/156854012x650197
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny of the genera Palaemon and Palaemonetes (Decapoda, Caridea, Palaemonidae) from a European perspective

Abstract: A molecular phylogenetic study by Murphy & Austin (2003)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 20 publications
(25 reference statements)
1
13
0
Order By: Relevance
“…As a result, here we provide the largest mitogenome phylogeny for the genus Palaemon to date, where all nodes were strongly supported. Although extensive worldwide phylogenetic analyses have been performed in Palaemon, they were always based on a few mitochondrial (cox1 and 16S rDNA) and/or nuclear (histone 3 and 18S rDNA) genes [7][8][9][10]. In this regard, our trees showed a general agreement with the last phylogenetic assessment of the genus [8], supporting the current non-monophyletic status of Palaemon since the South African species P. capensis was included in the lineage comprising the Macrobrachium species.…”
Section: Plos Onesupporting
confidence: 78%
See 1 more Smart Citation
“…As a result, here we provide the largest mitogenome phylogeny for the genus Palaemon to date, where all nodes were strongly supported. Although extensive worldwide phylogenetic analyses have been performed in Palaemon, they were always based on a few mitochondrial (cox1 and 16S rDNA) and/or nuclear (histone 3 and 18S rDNA) genes [7][8][9][10]. In this regard, our trees showed a general agreement with the last phylogenetic assessment of the genus [8], supporting the current non-monophyletic status of Palaemon since the South African species P. capensis was included in the lineage comprising the Macrobrachium species.…”
Section: Plos Onesupporting
confidence: 78%
“…Specifically in Palaemon, extensive worldwide phylogenetic analyses have been performed revealing the need for further systematic rearrangements. Two studies suggested to synonymise Palaemonetes, Exopalaemon and Coutierella with Palaemon since their paraphyly was demonstrated [9,10]. This new genus Palaemon, redefined by De Grave & Ashelby [2], mainly grouped species according to their biogeographical distribution.…”
Section: Introductionmentioning
confidence: 94%
“…An introduced species, Palaemon macrodactylus, has also been reported in the Gulf of Cádiz, in the Guadiana, Guadalquivir, Guadalete, San Pedro and Salado estuaries (Cuesta et al 2004, González-Ortegón et al 2005, in Cascais, western Portugal (Santinho 2009) and in the Balearic Islands as larvae (Torres et al 2012). Finally, , Cuesta et al (2012) and Cartaxana (2015) found, by analysing the variation in mtDNA, that there is no reason to recognize Palaemon garciacidi (a species described by Zariquiey-Alvarez 1968) as a species distinct from P. longirostris. In addition, larvae of Ascidonia flavomaculata were captured in Portugal by Paula (1987).…”
Section: Taxonomic Groupsmentioning
confidence: 93%
“…Hence, according to this theory, dispersed distributions of heterochromatin (interstitial or telomeric) have an older phylogenetic status. Iii) Recent molecular phylogenetic studies have suggested that genus Exopalaemon should be included within Palaemon [8, 33]. Among Exopalaemon , karyological analysis of E. modestus and E. carinicauda , have shown a diploid chromosome number of 90 [34, 35].…”
Section: Discussionmentioning
confidence: 99%